Phytochemical Analysis and Antibacterial Activity of Methanol and Ethyl Acetate Extracts of Detarium microcarpum Guill. & Perr. - Dahiru, Mubarak Muhammad; Abaka, AbudulAzeez Mumsiri; Artimas, Susan Pwakangdi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
This research aimed to investigate the phytoconstituents and antibacterial effects of methanol and ethyl acetate stem bark extracts of Detarium microcarpum (DM). The phytochemicals were detected and quantified while the antibacterial activity against Escherichia coli, Staphylococcus aureus, and Salmonella typhi was established determining the zone of inhibition (ZI), minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). Phytochemical screening showed alkaloids (16.33% ±0.88) were present in the methanol extract only while saponins and flavonoids were detected in concentrations of 31.00% ±2.31 and 21.01% ±2.33 respectively for the methanol extract and 21.67% ±1.76 and 38.01% ±1.16, for the ethyl acetate. The methanol extract exhibited the highest ZI on S. aureus (21.3 mm ±1.11) with its least inhibition observed on E. coli (6.5 mm ±0.77) while the ethyl acetate extract demonstrated the highest ZI on S. typhi (19.1 mm ±2.01). S. typhi exhibited more sensitivity to DM extracts at the least concentrations of 12.5 mg/ml (methanol) and 25 mg/ml (ethyl acetate) while the MBC results showed that the 12.5 mg/ml and 25 mg/ml were the effective respective concentration for methanol and ethyl acetate extracts against S. typhi. Conclusively, DM exhibited an antibacterial effect against the test organisms with notable inhibitory and bactericidal effects.